A Study on Benefits Associated with Brand in the Purchase of Mysore Silk Saree - Aishwarya S Arahunasi; Juin Choudhury (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
Introduction: A Mysore Silk Saree is a very unique and enjoyable purchase for customers since it embodies a weaving of both material and intangible advantages. These sarees are of high quality and are expertly woven with finest silk, which ensures both durability and opulent aesthetics. Customer relationship management is crucial for the business of Mysore silk sarees because it focuses on maintaining a strong market presence while prioritizing customer satisfaction and accordingly the customer is turning into a key factor for the little and huge organizations. Aims and objectives: This research paper aims to study the complex relationship between consumer preferences, brand influence, and the traditional realm of buying Mysore silk sarees. It covers the relationship with business partners, regulators and investors and society in large. The aim of the study is also investigate customer behaviors and opinions towards buying Mysore Silk Sarees. It examines the branding components and how it affects the consumers decisions. It studies the complex relationship of consumer preferences, brand influence, and the traditional realm of buying Mysore silk sarees and understanding the customer needs, that includes design, color, pattern, quality, trust, celebrity endorsement, brand name, tradition. Place and Duration of Study: The study was conducted in Bangalore city, with also include people who might be the visitors to the city. Duration of the study was 2 months from May and June 2023. Study Design: The research design used is Descriptive design. In this study design, features, behaviors, or occurrences are carefully observed and described without the usage of manipulative factors. It seeks to give readers a precise and thorough overview of the topic under study. This design gives a better understanding to the researchers into current patterns, linkages, and trends, so that it will give them a scope of further research opportunities. Data has been gathered by using both statistical methods and theme classification for qualitative inputs. When navigating the world of Mysore silk saree procurement, this analytical phase sought to identify trends, patterns, and recurring themes relating to the perceived advantages associated with brands. Results: The research results provide brands, producers, and marketers with concrete ideas on how to incorporate the observed advantages into their branding strategy and strengthen consumer loyalty and trust. Mysore silk creates a brand image in the customer’s mindsets and maintains a long-term relationship with their customers. Conclusion: Purchasing a Mysore Silk Saree is an act of supporting regional craftspeople, conserving history, and boosting local economies. Additionally, these sarees became symbols of distinction, denoting not just individual pride but also a group ties to a past that still permeates modern life.